Technological innovation in Small and Medium Enterprises: A bibliometric analysis - Roni Budianto; Agung Praptapa; Eliada Herwiyanti; Puji Puji; Eko Suyono; Oman Rusmana (Goodwood Publishing, 2022)
Purpose: The objective of this study is to find out the development of SMEs in the digital era. Research Methodology: The authors used the Scopus database and searched for articles containing keywords such as